Which role do lacewings and ants play as predators of the citrus leafminer in Spain? - Urbaneja,A.=700 1 Muñoz, A.; Garrido, A.; Jacas, J.A.
(Es, En)
ilus., 21 ref.
Keywords: CHRYSOPERLA CARNEA; PHYLLOCNISTIS CITRELLA; CONTROL BIOLOGICO; DEPREDADORES; CITRUS; ESPAÑA